Experiments in Buddhist-Christian encounter: from Buddha-nature to the divine nature - Feldmeier, Peter (Orbis Books, 2018)
"Feldmeier explores connections and divergences between Buddhist and Christian spirituality by utilizing Christian figures like Meister Eckhart and St. John of the Cross to reflect upon Buddhist positions and teachings like Buddha-Nature and the Zen Oxherding Pictures. Feldmeier is well-versed in the metaphysical nuances of Buddhism and Christianity, but seeks in this volume to emphasize the spirituality of both faiths and to suggest how dialogue might change one's way of thinking about one's own faith (not just reveal alignments between the two)"--